(untitled) (Applied Biological Research, 2014)
The effect of feed moisture, screw speed and barrel temperature on colour coordinates of re-fabricated rice grains were investigated in a co-rotating twin-screw extruder using response surface methodology. The rice flour obtained from broken rice (< 1/8th- was used in the study. The screw speed was set at five levels between 49 and 150 rpm, barrel temperature between 59 and 110oC and feed moisture between 31 and 45%. All colour coordinates of re-fabricated grains evaluated - (total colour difference) and hue angle were significantly affected by the three process variables. Barrel temperature was the most significant variable with quadratic effect on a* . Response surface regression models were established to correlate the colour coordinates of re fabricated rice grains to the process variables. The optimized extrusion conditions for preparation of re-fabricated grains were 38%, moisture content, 130 rpm screw speed and 89°C barrel temperature. A significant change was observed in maillard precursors i.e. sucrose, glucose, fructose and maltose levels of re-fabricated rice obtained at optimum extrusion